2019
DOI: 10.3389/fnins.2019.00928
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Cuneate Nucleus in the Acupuncture Inhibition of Drug-Seeking Behaviors

Abstract: Our previous studies have shown that acupuncture suppresses addictive behaviors induced by drugs of abuse, including cocaine, morphine and ethanol, by modulating GABA neurons in the ventral tegmental area (VTA) and dopamine (DA) release in the nucleus accumbens (NAc). The mechanisms by which the peripheral signals generated by acupoint stimulation are transmitted to brain reward systems are largely unexplored. The present study aims to investigate the role of spinal dorsal column (DC) somatosensory pathways in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In experimental studies, acupuncture with manual twisting for 1 min 56 or acupuncture for 20 s 57 at HT7, but not at LI5, reduced foot shock-induced reinstatement cocaine-seeking behavior 56 or cocaine-induced locomotion activity 57 . Similarly, acupuncture at HT7, but not at LI5, markedly reduced reinstatement of cocaine-seeking, c-Fos expression and pCREB activation in the NAc shell 56 , and reduced self-administration behavior 58 .…”
Section: Discussionmentioning
confidence: 88%
“…In experimental studies, acupuncture with manual twisting for 1 min 56 or acupuncture for 20 s 57 at HT7, but not at LI5, reduced foot shock-induced reinstatement cocaine-seeking behavior 56 or cocaine-induced locomotion activity 57 . Similarly, acupuncture at HT7, but not at LI5, markedly reduced reinstatement of cocaine-seeking, c-Fos expression and pCREB activation in the NAc shell 56 , and reduced self-administration behavior 58 .…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, the neural pathway is the mechanism involved in acupuncture [43], which is applied to nervous system diseases [44]. e effect of acupuncture was blocked by local anesthetic injection in a rat model [45], indicating that peripheral sensory nerves are involved in the action of acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the neural pathway is the mechanism involved in acupuncture [ 43 ], which is applied to nervous system diseases [ 44 ]. The effect of acupuncture was blocked by local anesthetic injection in a rat model [ 45 ], indicating that peripheral sensory nerves are involved in the action of acupuncture. The mechanical connective tissue reaction instead of neural mechanism in FSN treatment was first investigated in a rabbit model in 2012 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized placebo-controlled study done with human subjects, Yang et al also found that acupuncture at specific acupoints can increase people's ability to abstain from alcohol use [4]. While acupuncture's mechanism of action is not entirely understood, there is some evidence that acupuncture can suppress drug-seeking by modulating the mesolimbic dopamine (DA) system [30,31]. The DA system plays an important role in the desire to seek safety and positive experiences, but excessive arousal of this system can cause feelings of urgency and craving [2].…”
Section: Background 21 Transcutaneous Electric Acupoint Stimulation (...mentioning
confidence: 99%